MAKE A VIRUS AND ANTIVIRUS BY USING VISUAL BASIC 6.0 - Setiadi Wedasmara; Hariyanto Hariyanto Skom, MMsi (Jurnal Sistem Informasi, 2009)
Amid the current development of information technology, automation andcomputerization is the one thing that has become a primary need for the community,ranging from the manufacturing process until the data storage is done by computer,without thinking about how risk that arises when there are no responsible parties whouse the computer as media to make money quickly, such as theft of datamanipulation, data intrusion or even destruction of data by a cracker.Amid the current technological developments cyber crime cont inues to accompanyany extent to information technology develops, many hackers and crackers whoexploit the weaknesses of a computer system using a virus, worm, keylogger or othermedia used for data theft, therefore, the working system of an operating sys tem andmaterials that may damage it should be more understandable to the process of datasecurity.